Direct ink writing of silicon-based anodes for Li-ion batteries - Arutselvan Pranav Ganesh (Nanyang Technological University, 2023)
The rise in use of electric vehicles, portable electronics, etc. has increased the demand for electrochemical energy storage devices (EESD) such as supercapacitors (SC) and rechargeable batteries. Among the different EESDs, the lithium-ion battery (LIB) is the most promising option due to its high power and energy densities, long service life, and eco-friendliness. However, the commercial LIBs available are mostly based on sandwich-shaped graphite electrodes produced by slot-die coating or doctor blade coating (DBC) that was found to limit battery performance. Graphite has relatively low specific capacity compared to other materials like silicon and the thick “sandwich” structure slows down the ion transportation between the electrolyte and electrode. A possible solution was to create silicon-based porous structure electrodes using direct ink writing (DIW) to reduce ion diffusion length and enhance the capacity of the battery by increasing active material loading. This was explored by printing a 15mm circular spiral pattern on battery casing. Before printing the electrodes, the printing parameters such as air pressure, concentration and molecular weight of binder, tip size, dispersant, viscosity, etc. were studied to achieve ideal printing set-up. Subsequently, it was found that the printed electrodes could sustain higher active material loading, as the coated electrode cracked when tested with a similar amount of active material. Moreover, the printed electrode had favourable cross-sectional morphology, proving the benefits of DIW over traditional coating methods. However, further battery performance analysis is needed to evaluate the use of silicon-based printed electrodes in LIBs.